Pearson, David, Books as History: The Importance of Books Beyond Their Texts, London: British Library, 2011. Book Ownership in Stuart England, Oxford: Oxford University Press, 2021 - Little, Geoffrey (Mémoires du livre / Studies in Book Culture, 2026)
David Pearson’s 2011 work Books as History successfully argues for the study of the book as an historical actor and agent. He emphasizes that a book’s design, type, binding, and more can tell us much about the era in which a book was produced and the pressures or tensions to which it was responding. His 2021 monograph, Book Ownership in Stuart England, allows Pearson to expand on these themes by examining characteristics of book use, ownership, and circulation during a significant period of British history. Both works are situated within the ongoing debate about the book’s future in an age of digitization, in which Pearson’s framework for understanding books as material and historical actors proves a timely corrective to predictions of print’s obsolescence.